Pelatihan Pembuatan Keripik dan Nugget Daun Beluntas Beserta Pengemasan dan Pemasarannya di RT.05 RW.01 Wiyung Surabaya - Luqman Agung Wicaksono; Andre Yusuf Trisna Putra; Anugerah Dany Priyanto (Journal of Science and Social Development, 2020)
Wiyung is a district in Surabaya, East Java, Indonesia. A long time ago, this district used to be an agricultural area. However, currently some of the area used to agricultural land has been used for the construction of residential and commercial activity areas. One of the areas in the wiyung district is RT.05 RW.01 where this area is known as quite densely population. Based on the situation analysis, in the midst of crowded housing in narrow alleys at RT.05 RW.01 Wiyung, many beluntas plants (Pluchea indica) were found growing wild in people's yards. In fact, this beluntas plant has the potential to be used as various food products which can indirectly improve the economic level of the surrounding community. Therefore, a community service program is needed to provide training on how to use the beluntas plants into processed food products, especially beluntas chips and beluntas nuggets, along with how to package and its market. The method used in this community service includes a participatory approach with survey activities and training both theoretical and practical. At the end of this community service activity, it was seen that the participants were able to process beluntas leaves into chips and nuggets along with their packaging and labeling.